Orthodontic management of an erupted mesiodens: a case report - Abu Bakar, Noraini (IIUM Press, International Islamic University Malaysia, 2017)
Introduction: Hyperdontia is the condition of having supernumerary tooth, or teeth, which appear in addition to the regular number of teeth. It is a developmental anomaly and has been argued to arise from multiple aetiologies. It may remain embedded in the alveolar bone or can erupt into the oral cavity. Mesiodens is a supernumerary tooth located in the anterior maxilla, placed palatally or in between the maxillary central incisors. It may be single or paired, erupted or impacted and at times even inverted. Aesthetic or functional problems are two main issues associated with mesiodens.This case report demonstrates the orthodontic management of a case of a nonsyndromic male patient with conical type supernumerary tooth at the maxillary anterior region with a Class I malocclusion complicated by palatally erupted upper right lateral tooth with Bolton discrepancy. Good aesthetic and functional result achieved at the end of treatment.